Outbreaks of Infection Caused by Community-Acquired Methicillin-Resistant Staphylococcus aureus in a Canadian Correctional Facility - Cheryl L Main; Padman Jayaratne; Allan Haley; Candy Rutherford; Fiona Smaill; David N Fisman (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) has been identified in prison settings in the United States. The present study investigated two clusters of skin and soft tissue infection caused by community-acquired (CA) MRSA in a correctional facility in southern Ontario.